The Role of Human Capital in the Economic Development of Countries - S. K. Baidybekova; S. B. Sauranbay (Экономика: стратегия и практика, 2022)
Human capital is the main valuable resource of states, the development of the economies of countries and regions as a whole. In many works of scientists and economists, the problems of development, formation, and effective use of human capital are reflected. In a market economy, the development competitiveness of countries depends on the level of progress, which includes the introduction of new advanced innovations. For determining the level of development of countries, the indicators are taken as volume of gross domestic product, life expectancy, level of education and etc. The main factor on development and formation of human capital is education. In a market, the role of education has increased by providing socio-economic and competitive education. The main task of article is the creation of qualified education system in necessary conditions for each individual, which will be contributed to the development and improvement of human capital.    The purpose of the study is to consider the rating of human capital in separate countries, their role in the economy and factors of human development. The main sources of the study were data from electronic resources and from the World Bank. The following tasks were solved: reflects the rating of human capital by country and region; the role of human capital in the economies of individual countries is determined; reflects the main measures for the development of human capital in countries and regions; tools and criteria for the development and improvement of human capital are defined.